Identity Conflict in Nigeria: An Analytical Deconstruct - Jah, Emmanuel Achus; Iruonagbe, Felicia; Nanpon, Nandang Freeman (Kashere Journal of Politics and International Relations, 2023)
With the plurality in Nigeria, the society is laden with diversity which is supposed to be a source of strength but has become an albatross for the nation. When governance in Nigeria is predicated on identity (Political, Ethnic and Religious) the nation suffers tremendously from constant conflict which costs the nations a huge loss in terms of human and material resources. Therefore Ethnic and religious identities have now found expression in politics and same ethnicity and religion are critical factors in Nigerian politics. The Objective of this inquiry is to explain how identity influences conflict in Nigeria. The study leverages on secondary data and adopts Structural Conflict Theory to explain the problematic. The causes of identity conflict (ethno-religious and political identity) in Nigeria are Intolerance, Conflict Entrepreneurs, Stereotypes and ethnic profiling, Ethnic, Religious and Political Supremacists, Resources, Colonial Legacy and State failure while the consequences of identity conflict in Nigeria are Political polarization/Majoritarian rule, Ethno-religious Strives, Mutual Suspicion, Loss of Nationalism, Marginalization, Loss of Lives and Property. The study recommends that Federal Characters Commission should be seen to be transparent, accountable and fair to all, the judiciary must be seen to dispense justice without prejudice, politicizing ethnicity and religion be voided by enabling laws, Government must put strong, workable, institutional and legal framework for diversity management. The study thereafter concludes that value reorientation be part of the hallmarks of governance Nigeria so that all and sundry will have sense of belonging and not exclusion.